Digitalization of Notary Deeds In The Era of Industrial Revolution 4.0 In Facing The Covid-19 Pandemic - Yoga Andriyanto, SH; Dr. Rusdianto Sesung, SH, MH (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Purpose of this research is first, to analyze the digitization of deeds and notary deeds that do not conflict with the Law on Notary Position. Second, to analyze legal certainty in changing the behavior of notaries who use digital media in the era of the industrial revolution 4.0 and facing the Covid-19 pandemic when making and storing minimum deeds. This research uses normative legal research methods. This research concludes, firstly: Notary deed and minuta deed are very important state documents, so that in their storage the Notary is obliged to maintain and safeguard them properly, regulated in UUJN Article 1 point 13. Storage of Notary deed minuta documents using electronic media has not been regulated in UUJN, however, Article 6 of the ITE Law considers the validity of an electronic document, even though the evidence according to Article 1866 of the Criminal Code and Article 184 of the Criminal Procedure Code does not explain the existence of electronic evidence, in which a notary deed is an authentic deed in accordance with UUJN Article 1 point 1. Second: Changes in the work behavior of Notaries In the era of the industrial revolution 4.0 and facing the Covid-19 pandemic, the creation and storage of digital notary deeds requires certainty and protection from the Government and the Indonesian Notary Association (INI). Digitalization as a form of notary adhering to health protocols and protection for minimum notary deeds from damage caused by natural disasters, fire and being eaten by termites and excess space.